Subcellular Localization of a Glycoprotein Released from Human Platelets upon Stimulation by Thrombin - R. Käser-Glanzmann; M. Jakábová; E.F. Lüscher (CHIMIA)
The treatment of washed, intact human blood platelets with 1 U/ml of thrombin for 5 min at 37 °C is linked to the disappearance from the particulate fraction of the homogenized cells of a protein band discernible in the SDS-polyacrylamide gel electrophoresis pattern of untreated platelets. Accordingly, this material was termed thrombin sensitive protein (TSP) by its discoverers, who also presented evidence that TSP is a glycoprotein of a molecular weight of 190,000. The present work describes the localization of TSP in human platelets. TSP is not a membrane constituent, but associated with orgenelle fractions in the region of higher densities. It therefore is not, as originally suggested, a direct substrate for thrombin on the platelet surface, but takes part in the platelet release reaction upon a variety of external stimuli. An apparent molecular weight of 150,000 was found for TSP; this value coincides with the one reported for so-called glycoprotein I, which, different from TSP, is a membrane constituent.